Fostering collaborative partnerships in pharmacy education: a landmark MoU and loa signing ceremony / Mohd Nadzri Mohd Najib … [et al.] - Mohd Najib, Mohd Nadzri; Othman, Mohd Izani; Mokhtar, Nur ‘Ainun; Ibrahim, Nur Alyaa; Hanif, Mohd Ikhmal (UiTM Global @ Office of International Affairs, 2024)
In a significant stride towards fostering collaboration and innovation in pharmacy education and research, a momentous Memorandum of Understanding (MoU) and Letters of Agreement (LoA) signing ceremony took place on 21 November 2023 at Perpustakaan Tun Abdul Razak (PTAR) Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia. The five MoUs and three LoAs signed between UiTM and the eight institutions are in line with UiTM's aspiration to become globally renowned by 2025. The ceremony exemplifies UiTM’s commitment to forging strategic partnerships and fostering collaboration on a global scale.